(9x-6)3power=9

Simple and best practice solution for (9x-6)3power=9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (9x-6)3power=9 equation:


Simplifying
(9x + -6) * 3power = 9

Reorder the terms:
(-6 + 9x) * 3power = 9

Reorder the terms for easier multiplication:
3eoprw(-6 + 9x) = 9
(-6 * 3eoprw + 9x * 3eoprw) = 9
(-18eoprw + 27eoprwx) = 9

Solving
-18eoprw + 27eoprwx = 9

Solving for variable 'e'.

Move all terms containing e to the left, all other terms to the right.

Reorder the terms:
-9 + -18eoprw + 27eoprwx = 9 + -9

Combine like terms: 9 + -9 = 0
-9 + -18eoprw + 27eoprwx = 0

Factor out the Greatest Common Factor (GCF), '9'.
9(-1 + -2eoprw + 3eoprwx) = 0

Ignore the factor 9.

Subproblem 1

Set the factor '(-1 + -2eoprw + 3eoprwx)' equal to zero and attempt to solve: Simplifying -1 + -2eoprw + 3eoprwx = 0 Solving -1 + -2eoprw + 3eoprwx = 0 Move all terms containing e to the left, all other terms to the right. Add '1' to each side of the equation. -1 + -2eoprw + 1 + 3eoprwx = 0 + 1 Reorder the terms: -1 + 1 + -2eoprw + 3eoprwx = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -2eoprw + 3eoprwx = 0 + 1 -2eoprw + 3eoprwx = 0 + 1 Combine like terms: 0 + 1 = 1 -2eoprw + 3eoprwx = 1 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 128-N=46 | | 6x^2-400=0 | | y=3x^4-2x^3+74x^2-50x-25 | | 25x^2+1=37 | | 6x^2-400=9 | | 4e=36 | | 2/3*54 | | (9-6)3=9 | | 5/6x-5/6=5 | | 5(3-x)+2(3-x)=14 | | 3a+b-45=2a+4b-465.23+-a+507.23b | | 2x+8x-20=90 | | 15x+8=2x+2 | | -3x+4=-5x-9 | | 1/2m+3 | | 2.16+2=72 | | 6+2/3y=-12 | | 3x-(7x-4)=5x-(2x+10) | | z/17=-19 | | 14-3/4x | | 4-3x=5(x+4) | | 3a+b-45=2a+4b+465.23+-a+507.23b | | 19=4y+7 | | 29+0.15x=20+0.25x | | 2x+3-5x=5x-15+6 | | (2x+1)(2x-1)=4x | | 4y+2=-8/3(8-12y) | | 3a+b-45=2a+4b+465.23+a+507.23b | | 15+.25x=20+0.05 | | 2x+4=9+6x | | -4(x-9)=42 | | 5x-12+7x+4= |

Equations solver categories